74.1k views
3 votes
Consider the following graph of two functions.f(2) + (-1)Step 2 of 2: Find f(2) + (-1)Enable Zoom/Pan8(x) = x2 - 2x - 1f(x) = -x+1-10

Consider the following graph of two functions.f(2) + (-1)Step 2 of 2: Find f(2) + (-1)Enable-example-1

1 Answer

2 votes

Given the graphed functions:


\begin{gathered} f(x)=-x+1 \\ \\ g(x)=x^2-2x-1 \end{gathered}

Let's find f(2) + g(-1).

f(x) is the represented by the line.

From the graph, we have:

f(2) = -1

g(x) is represented by the parabla.

From the graph, we have:

g(-1) = 2

Hence, to add both values we have:

f(2) + g(-1) = -1 + 2 = 1

ASWER:

1

User Abtin Rasoulian
by
5.2k points